Pre-extraction affects the mycelial bioconversion potential of Typha spp. and Salix spp. biomass residues - Petros, Peter; Lankinen, Pauliina; Adamczyk, Sylwia; Meneguzzo, Francesco; Tagliavento, Luca; Kaipanen, Kalle; Kilpeläinen, Petri; Kaseva, Janne; Lång, Kristiina; Mikkonen, Kirsi S.; Jyske, Tuula M. (Elsevier, 2026)
Mycelial bioconversion is a promising industrial avenue for transforming a wide array of bio residues and feedstocks into higher added value chains via application of filamentous fungi. Little research has been conducted on the bioconversion efficacy of pre-extracted biomass (PEB) from feedstocks suitable for paludiculture, a sustainable cultivation practice for degraded peat soils. This study investigated the bioconversion ability of five white-rot basidiomycete fungi on pre-extracted and unextracted biomasses derived from two mainstream paludicultural crops: short-rotation coppice willow (Salix schwerinii x Salix viminalis) and perennial cattail grass (Typha latifolia). Willow biomass fed through pressurised hot water extraction (PHWE) and hydrodynamic cavitation extraction (HCE) and cattail biomass via HCE were utilised. During a mycelial bioconversion incubation, Trametes sp. showed fastest hyphal extension rate (4.1 ± 0.35 mm/day) on willow PEBHCE and Pleurotus floridanus hyphal extension was fastest on cattail PEBHCE and unextracted biomasses (4.89 mm/day). Hyphal extension rates across all fungal species were generally faster on PEBHCE compared to unextracted biomasses. Post-incubation analyses showed Fomes fomentarius yielded highest ergosterol content (marker of fungal biomass) across all plant biomasses compared to other fungal species (LSM = 64.0129 μg/g d.w., p < 0.0001). Pre-extraction via PHWE significantly inhibited mycelial bioconversion efficacy both in terms of hyphal extension and ergosterol content. In contrast, pre-extraction via HCE did not inhibit myceliation efficacy of willow and cattail biomass. These results highlight the novel value of PEB from large-scale paludiculture, and likely other cascaded lignocellulose biomasses, as viable bio-residue feedstocks towards industrial mycelial bioconversion applications.
Keywords: bioconversion; biomass; ergosterol; fungi; paludiculture; pre-extraction